Lithium Difluorophosphate: A Boon for High Voltage Li Ion Batteries and a Bane for High Thermal Stability/Low Toxicity: Towards Synergistic Dual Additives to Circumvent this Dilemma. Issue 6 (19th January 2023) - Kubot, Maximilian; Frankenstein, Lars; Muschiol, Elisabeth; Klein, Sven; Esselen, Melanie; Winter, Martin; Nowak, Sascha; Kasnatscheew, Johannes
Abstract: The specific energy/energy density of state‐of‐the‐art (SOTA) Li‐ion batteries can be increased by raising the upper charge voltage. However, instability of SOTA cathodes (i. e., LiNi y Co x Mn y O2 ; x + y + z =1; NCM) triggers electrode crosstalk through enhanced transition metal (TM) dissolution and contributes to severe capacity fade; in the worst case, to a sudden death ("roll‐over failure"). Lithium difluorophosphate (LiDFP) as electrolyte additive is able to boost high voltage performance by scavenging dissolved TMs. However, LiDFP is chemically unstable and rapidly decomposes to toxic (oligo)organofluorophosphates (OFPs) at elevated temperatures; a process that can be precisely analyzed by means of high‐performance liquid chromatography–high resolution mass spectroscopy. The toxicity of LiDFP can be proven by the well‐known acetylcholinesterase inhibition test. Interestingly, although fluoroethylene carbonate (FEC) is inappropriate for high voltage applications as a single electrolyte additive due to rollover failure, it is able to suppress formation of toxic OFPs. Based on this, a synergistic LiDFP/FEC dual‐additive approach is suggested in this work, showing characteristic benefits of both individual additives (good capacity retention at high voltage in the presence of LiDFP and decreased OFP formation/toxicity induced by FEC). Abstract : A stabilizing influence : The instability of LiNi x Co y Mn z O2 cathodes triggers electrode crosstalk and contributes to severe capacity fade. Lithium difluorophosphate (LiDFP) as electrolyte additive boosts high voltage performance by scavenging dissolved transition metals yet is chemically unstable. However, a synergistic LiDFP‐fluoroethylene carbonate dual‐additive approach is found to show good capacity retention at high voltage and decreased decomposition.